Corporate reputation's mediation in gen z's job application intentions in west Kalimantan - Megawati, Megawati; Saputra, Pramana; Jaya, Arman; Hendri, M. Irfani; Fauzan, Rizky (Institute of Computer Science (IOCS), 2025)
This study aims to analyze the influence of employer attractiveness, social media, and corporate reputation as mediating variables on the job application intentions of Generation Z in West Kalimantan. The population for this research consists of 194 Gen Z respondents from West Kalimantan. The study employs a quantitative approach, collecting data through an online survey using Google Forms. The data is analyzed using Structural Equation Modeling (SEM) with the help of the SMARTPLS 4.0 statistical application. Based on the analysis, it is concluded that employer attractiveness does not significantly encourage Generation Z to apply for jobs in West Kalimantan. In contrast, social media effectively boosts their interest in applying. Both employer attractiveness and social media influence corporate reputation, which in turn encourages Generation Z to apply for jobs. Additionally, a strong reputation enhances the effects of employer attractiveness and social media in attracting applicants.